The effect of brown algae (Sargassum sp.) gel on the number of osteoclasts in periodontitis rats - S. Abdurrohman, Muhamat Muhtar; Praptiningsih, Rahmawati Sri; Yulistinawati, Yulistinawati (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Alveolar bone resorption in periodontitis is caused by increased activation of osteoclasts, causing an imbalance of bone remodeling. Periodontitis treatment can be done mechanically with Scaling and Root Planing and accompanied by metronidazole. Antibiotics have long-term drawbacks and can cause allergies, thus requiring an alternative to natural topical drugs such as brown algae gel. This study aimed to to analyzed the effect of brown algae gel (sargassum sp) on the number of osteoclasts of alveolar bone in periodontitis rats. Methods: The research method was a True Experimental with a pretest-posttest-only control group design. Rats were divided into three groups; negative control (K-) was not given any treatment, positive control (K+) was given metronidazole ties plus 25% concentration, and the treatment group (KP) was given brown algae gel (Sargassum sp) 75% concentration. Data were analyzed by Friedman and Kruskal Wallis test. Results:There was a significant difference in the number of osteoclasts on days 8, 10, and 12, the decrease in the number of osteoclasts was higher in the brown algae treatment group than the negative control group (p=0.051). In the positive control group, there was a significant difference in the decrease of the number of osteoclasts compared to the brown algae treatment group (p=0.029). The number of osteoclasts was significantly different on day 12 (p=0.026).Conclusion: Adhering brown algae (Sargassum sp.) gel decreases osteoclasts in periodontitis rats.Keywords: bone remodeling; bone resorption; brown algae gel (sargassum sp.); osteoclasts; periodontitis.